Ghana's Economic and Agricultural Transformation Past Performance and Future Prospects - Diao, Xinshen; Hazell, Peter; Kolavalli, Shashidhara; Resnick, Danielle (Oxford University Press, 2019)
Many African countries have experienced unprecedented rates of economic growth in recent years, yet their economic transformations display features that could constrain their future growth prospects. Particularly troublesome have been patterns of urbanization without industrialization, rapid growth of low-productivity jobs in the informal economy, and a neglected agricultural sector with increased need for imported foods. Using Ghana as a case study, this book explores the challenges and opportunities of these patterns of transformation. By combining a historical and political perspective with in-depth empirical analysis of the performance of the broader economy and the agricultural sector since the economic reforms of the 1980s, the book considers viable policy options for Ghana and discusses the implications for other African countries.